Ouabain exacerbates activation-induced cell death in human peripheral blood lymphocytes - Esteves,Mabel B. (2005)
Lymphocytes activated by mitogenic lectins display changes in transmembrane potential, an elevation in the cytoplasmic Ca2+ concentrations, proliferation and/or activation induced cell death. Low concentrations of ouabain (an inhibitor of Na+,K+-ATPase) suppress mitogen-induced proliferation and increases cell death. To understand the mechanisms involved, a number of parameters were analyzed using fluorescent probes and flow cytometry. The addition of 100nM ouabain to cultures of peripheral blood lymphocytes activated with 5µg/ml phytohemagglutinin (PHA) did not modify the increased expression of the Fas receptor or its ligand FasL induced by the mitogen. However, treatment with ouabain potentiated apoptosis induced by an anti-Fas agonist antibody. A synergy between ouabain and PHA was also observed with regard to plasma membrane depolarization. PHA per se did not induce dissipation of mitochondrial membrane potential but when cells were also exposed to ouabain a marked depolarization could be observed, and this was a late event. It is possible that the inhibitory effect of ouabain on activated peripheral blood lymphocytes involves the potentiation of some of the steps of the apoptotic process and reflects an exacerbation of the mechanism of activation-induced cell death.